Recent History of Federal Support For Rural Education - E. Robert Stephens (Educational Considerations, 1994)
Rural interests have long argued that the federal government is insensitive to the needs of rural schools, or worse, that a widespread anti-rural, pro-urban bias permeates all levels of the federal policy communities.